2016
DOI: 10.1039/c6ra18534g
|View full text |Cite
|
Sign up to set email alerts
|

First-principles insight into the photoelectronic properties of Ge-based perovskites

Abstract: First-principles investigations were performed to elucidate the effects of A and X in Ge-based MAGeX3 perovskites (MA = CH3NH3+; X = Cl−, Br−, and I−) and AGeI3 (A = Cs+, CH3NH3+, HC(NH2)2+, CH3C(NH2)2+, and C(NH2)3+) on the photoelectronic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 30 publications
3
39
1
Order By: Relevance
“…[75] Theoretical studies have shown that these Ge halide perovskites exhibit promising optoelectronic properties for solar cell applications. [74][75][76][77][78][79][80][81] Taking CsGeI 3 as an example, the calculated band structure shows a direct bandgap at the Z point, as shown in Figure 7d. [75] The VBM consists of antibonding states of Ge 4s and I 5p orbitals.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[75] Theoretical studies have shown that these Ge halide perovskites exhibit promising optoelectronic properties for solar cell applications. [74][75][76][77][78][79][80][81] Taking CsGeI 3 as an example, the calculated band structure shows a direct bandgap at the Z point, as shown in Figure 7d. [75] The VBM consists of antibonding states of Ge 4s and I 5p orbitals.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…MAGeI 3 has an optical bandgap 1.63 eV which is greater in magnitude than that of MAPbI 3 (1.55 eV) and MASnI 3 (1.30), excellent hole and electron conducting behavior and better stability in air as compared to MaPbI 3 . However, Ge 2+ cation being smaller in size (73 pm) deviates from its regular [GeI 6 ] octahedral center as it replaces cation of much larger ionic radius as that of Pb 2+ (119 pm) and Sn 2+ (110 pm) . As a consequence, it forms three short GeI bonds (2.73–2.77 Å) and three long in GeI bonds (3.26–3.58 Å).…”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
“…However, Ge 2+ cation being smaller in size (73 pm) deviates from its regular [GeI 6 ] octahedral center as it replaces cation of much larger ionic radius as that of Pb 2+ (119 pm) and Sn 2+ (110 pm) . As a consequence, it forms three short GeI bonds (2.73–2.77 Å) and three long in GeI bonds (3.26–3.58 Å). The Ge‐based perovskites have been extensively studied by carrying computational work based on density functional theory (DFT) .…”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
“…However, in practice the Ge-based perovskites such as CsGeI 3 , MAGeI 3 , and FAGeI 3 displayed larger bandgaps (i.e., 1.63, 2.0, and 2.35 eV) than that of CH 3 NH 3 SnI 3 (1.30 eV) and CH 3 NH 3 PbI 3 (1.55 eV) [52]. The difference between experimental data and what we expected from high orbital energy is mainly due to the structural distortion of [GeI 6 ] octahedral as the small ionic radius (0.73 Å) of Ge 2+ substituting the bigger ionic radius of Pb 2+ (1.19 Å) or Sn 2+ (1.02 Å) [53]. Additionally, the Ge-based perovskites crystallize in polar space groups [54].…”
Section: Ge- Bi- Sb- and Cu-based Perovskitesmentioning
confidence: 64%